Teachers in higher education in Bahia: An analysis from the Annual Relationship of Social Information (RAIS) (Research, Society and Development, 2020)
This article presents research results using the Ministry of Labor and Employment's Annual Social Information (RAIS) database or source. The objective was to obtain information on the teaching staff of higher education institutions in Bahia and to analyze the profile of these periods in the period from 2008 to 2018. Eligible cut, no case of higher education teachers should be noted, without a selected period, Bahia won four more public education institutions, which have campuses in the interior of the state and for some time after employment for higher education teachers with master's degrees and doctorate and this insertion started at RAIS, although it represents some irregularity in the information about the public sector. The hypothesis that there was an increase in employment for higher education teachers in Bahia in the selected period, the objective of the work was analyzed if there was an increase and in what demographic characteristics. This exploratory study seeks to confirm some phenomena observed in the corridors of institutions, which is the increase in master documents and younger doctors and the predominance of women, but also as new policies for teacher remuneration, workload and degree. Nevertheless, the analysis of RAIS data, the results of this work are described on other databases such as E-MEC and GEOCAPES, which grant the number of masters and doctors in higher education institutions in the state.